Multiple copies of nodD in Rhizobium tropici CIAT899 and BR816. - van Rhijn, P J (1993)
Rhizobium tropici strains are able to nodulate a wide range of host plants: Phaseolus vulgaris, Leucaena spp., and Macroptilium atropurpureum. We studied the nodD regulatory gene for nodulation of two R. tropici strains: CIAT899, the reference R. tropici type IIb strain, and BR816, a heat-tolerant strain isolated from Leucaena leucocephala. A survey revealed several nodD-hybridizing DNA regions in both strains: five distinct regions in CIAT899 and four distinct regions in BR816. Induction experiments of a nodABC-uidA fusion in combination with different nodD-hybridizing fragments in the presence of root exudates of the different hosts indicate that one particular nodD copy contributes to nodulation gene induction far more than any other nodD copy present. The nucleotide sequences of both nodD genes are reported here and show significant homology to those of the nodD genes of other rhizobia and a Bradyrhizobium strain. A dendrogram based on the protein sequences of 15 different NodD proteins shows that the R. tropici NodD proteins are linked most closely to each other and then to the NodD of Rhizobium phaseoli 8002.